How ICT and Green Technologies Shape the Nexus Between Financial Development and Carbon Footprint: Evidence from an N-Shaped EKC - Topaloglu, Emre E.; Nur, Tugba; Yilmaz Ozekenci, Sureyya; Aydingulu Sakalsiz, Seren (Mdpi, 2025)
This study explores the effect of financial development, economic growth, ICT, green technologies, and strict environmental policies on environmental sustainability in the states of the European Union from 1996 to 2022. It also evaluates the EKC hypothesis and examines how ICT and green technologies moderate the linkage between financial development and carbon footprint. The Westerlund-Durbin-Hausman cointegration test is used for the long-run relationship. The FMOLS and CUP-FMOLS estimators are used to estimate the long-run elasticity coefficients, providing reliable results. The results reveal an inverted N-shaped linkage between GDP and carbon footprint in EU states, validating the EKC hypothesis. Furthermore, financial development has been found to increase carbon footprints, whereas green technologies, ICT, and stringent environmental regulations have been shown to mitigate these effects. Additionally, the interaction effects of ICT and green technologies with financial development demonstrate a reduction in the carbon footprint. These findings indicate that the EU should integrate the moderating role of innovation into policies addressing the pollution caused by financial development to achieve net-zero emission goals.
Keywords: carbon footprint; economic growth; financial development; ICT; green technology; EU states